Association of PON2 Gene Polymorphisms (Ser311Cys and Ala148Gly) With the Risk of Developing Type 2 Diabetes Mellitus in the Chinese Population - Ren, Huan; Tan, Sheng-Lan; Liu, Mou-Ze; Banh, Hoan L.; Luo, Jian-Quan (Frontiers in Endocrinology, 2018)
Background: The association between paraoxonase 2 (PON2) gene polymorphisms and type 2 diabetes mellitus (T2DM) has been extensively investigated in the Chinese population with conflicting results. In this study, we systematically evaluated the association between PON2 Ser311Cys and Ala148Gly polymorphisms and T2DM risk by pooling all relevant studies. Methods: We searched PubMed, Embase, CNKI, and Wanfang databases for the studies. The strength of association was determined by the allelic, homozygous, heterozygous, recessive, and dominant genetic models and measured as odds ratio (OR) and 95% confidence interval (CI), under fixed- or random-effect models. Results: There was no significant association between PON2 Ser311Cys polymorphism and T2DM under any of the genetic models: allelic (OR = 1.06, 95% CI = 0.77–1.45; P = 0.721), heterozygous (OR = 1.13, 95% CI = 0.87–1.45; P = 0.362), dominant (OR = 1.10, 95% CI = 0.80–1.51; P = 0.562), recessive (OR = 0.87, 95% CI = 0.48–1.58; P = 0.648), homozygous (OR = 0.94, 95% CI = 0.47–1.89; P = 0.865). Similarly, no significant association was found in PON2 Arg148Gly polymorphism under any of the models: allelic (OR = 1.17, 95% CI = 0.91–1.50; P = 0.218), heterozygous (OR = 1.28, 95% CI = 0.94–1.74; P = 0.117), dominant (OR = 1.25, 95% CI = 0.93–1.67; P = 0.142), recessive (OR = 0.99, 95% CI = 0.52–1.88; P = 0.973), homozygous (OR = 1.08, 95% CI = 0.57–2.07; P = 0.808). Conclusions: The PON2 Ser311Cys and Ala148Gly polymorphisms were not associated with the risk of developing T2DM in the Chinese population.